"Mosque Architectureâ€ Or Architecture of Mosque: A New Notions of Bengal During the Muslim Rule - Ahmed, Sumaiya (Journal of Islamic Architecture, 2016)
The mosque constitutes one of the most highly developed forms of religious architecture. With the rapid expansion of the Muslim community through conquests as well as missionary activities, it became necessary to set aside an enclosed area in cities or large towns for the purpose of established communal worship. Mosque architecture in the Muslim period exposes clearly its sacred identity, even it is continuously remarked, but in secular architecture, the ideas are not spiritually motivated in a cosmic sense. Definitely a structural idea and use of materials as well as its functional and aesthetic use play a role in determining what is expressed by it. The development of understanding of functional and aesthetic use of materials and technique with effective manner is depending on assimilated technologies. Integrated process of standard materials, skilled labor, innovative idea and socioeconomic as well as geographical factors may regard to constructing any magnificent architecture. The present study is an attempt to analyse and develop the structure, structural decoration and use of materials and design of the mosques during the Muslim period in Bengal.